Mental Activity on the Process of Language Acquisition - Kokok Djoko Purwanto (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2017)
In the process of speaking or writing, in fact we do mental activity that will be reflected on the language we perform, known as ‘Language Acquisition’. Most people do not realize that practicing language is a kind of extra-ordinary complicated skill. Using language seems natural for as a baby without being taught by anyone, he will grow along with his own language. From the age of one year until one and a half, the baby can produce the language that is identified as a word. Then the word-utterance becomes two words and so on, until they will finally enlarge as a complex sentence when he is four or five years old. After we have grown up, we speak as if we do not think, by the time we would like to say something, at the same time we produce sounds called language.Key words: mental activity, language acquisition, words